PENGARUH WAKTU AKTIVASI TERHADAP SIFAT FISIS DAN ELEKTROKIMIA SEL SUPERKAPASITOR DARI SABUT PINANG - Retno Handayani; Erman Taer (Komunikasi Fisika Indonesia, 2019)
The Carbon electrodes made from areca husk biomass materials have been successfully prepared and characterized. Preparation of carbon electrodes start with the pre-carbonization process, destruction of pre-carbon samples by using Ball Milling and sieving carbon powder for resulting particle size of <53 µm. Pre-carbonized powder is chemically activated using a 0.5 M KOH activator and continued by pellet forming by using Hydraulic Press. The carbonization process was carried out at a temperature of 600 oC using N2 gas followed by physical activation by using CO2 gas with a temperature of 900 oC for 1.5 hours, 2 hours and 2.5 hours. Physical properties analyzed include density, morphological structure and elemental content. The electrochemical properties were analyzed using the cyclic voltammetry (CV) method. The best density analysis result after carbonization-activation is 0.664 in SP-2.5 sample. The highest specific capacitance as high as 17.9 F / g found in the SP-1.5 sample.